The Effect of Realia (Real Object) Media on Students’ Vocabulary Skill at MIS Hikmatul Salridho - Khaidir, Nurul Annisa; Harahap, Yulia Sari (Journal of Educational Research and Humaniora (JERH), 2024)
The objective of the research is to know whether the effect of use Realia Media on students vocabulary knowledge at the fourth grade of elementary at HikmatulSalridho. Based on the statement above, this research used experimental design of collecting data, the class that will be tested is divided into two classes, class A and class B, class A as control class and class B as Experimental class. The experimental group is the group that will be a measured of whether the test is successful or not using realia media, while the control group is considered without using realia media. Based on the statement beside, the researcher choose the population of class IV students at Hikmatul Salridho School. Where, the first class was students of class IV – A (as experimental groups) and IV – B (as control group) of the MIS Hikmatul Salridho School. After analyzing the results of the research, the researcher obtained data about the scores of the teaching and learning process using Realia Media. The researcher concluded that there was any significant effect of applying was proved by the results of the pre-test scores before giving the treatment. And it can be seen that the results of the statistical calculations above where the value of (to) is higher than (tt). The researcher also found there were some difficulties in students' vocabulary by applying Realia Media, especially in remember the vocabulary. The Realia Media are very interested to be implemented to improve vocabullary skills. The researcher found that there is always improvement in the learning. It’s mean that the implementation of Realia Media to improve students’ vocabulary skills can make students more actived, motivated, and interested. From the explanation above, it means that teaching learning process by using Realia Media can improve students’ ability in English vocabulary skill.